Performance of Arabic Language Learning Participation at Ponpes Al-Ikhwan Serapuh ABC - Lusiana Sinaga; Tasnim Lubis (Tradition and Modernity of Humanity, 2025)
This study aimed to describe the performance of Arabic language learning participation at Al-Ikhwan Serapuh ABC Islamic Boarding School. The ethnographic method proposed by Spradley [1][2] was applied in this research, from collecting data to analyzing it. The participation theory uses the participation structure proposed by Philips, and the participation framework uses Goffman's opinion[3]. The data were text, co-text, and context on Arabic language learning situations. The data were collected through recordings, interviews and participant observation. This study focused on finding the patterns of participation performance in the Arabic language learning process in the classroom through an anthropolinguistic approach [4]. The study results showed that students' participation in learning Arabic is a performance of testing, confirming and curious. The pattern of participation obtained is important data that can describe the phenomenon of speaking activity.